2011
DOI: 10.1111/j.1537-2995.2011.03111.x
|View full text |Cite
|
Sign up to set email alerts
|

The volume of returned red blood cells in a large blood salvage program: where does it all go? (CME)

Abstract: Although overall the mean volumes of RBCs returned to the patients by intraoperative blood salvage were high, the actual volumes returned depended on the case mix. There appears to be an opportunity to use blood salvage more selectively to improve efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…Additionally, a minimum volume of blood processed has been shown to be necessary in order for ICS to be cost-effective. 25 Studies in which residual CPB contents were not processed may not have observed the cost benefit that was appreciated in the present study owing to insufficient volume of blood processed. Regardless, the significant cost savings that we observed indicates that ICS is cost-effective.…”
Section: Icsmentioning
confidence: 47%
“…Additionally, a minimum volume of blood processed has been shown to be necessary in order for ICS to be cost-effective. 25 Studies in which residual CPB contents were not processed may not have observed the cost benefit that was appreciated in the present study owing to insufficient volume of blood processed. Regardless, the significant cost savings that we observed indicates that ICS is cost-effective.…”
Section: Icsmentioning
confidence: 47%
“…39 This technique involves the collection of shed surgical or obstetric blood and its filtration, washing, concentration and re-administration once a sufficient quantity of blood has been collected. Only surgery involving high blood loss-such as cardiac, vascular, and orthopaedic procedures-warrants it use.…”
Section: What Strategies Are In Place To Minimise Inappropriate Transmentioning
confidence: 99%
“…22,23 Since ASB RBCs are only removed from the circulation for hours, not days or weeks, it is unlikely that storage lesions would be present. In fact, 2,3-DPG levels are thought to be normal in ASB RBCs, 24 but it is unclear how ASB and stored RBCs compare, and whether significant changes in 2,3-DPG occur in patients after receiving either ASB or stored RBCs.…”
Section: Introductionmentioning
confidence: 99%